Hyperpartisan news: Rethinking the media for populist politics. (May 2021) - Rae, Maria
Online media sites such as Breitbart News in the United States and The Canary in the United Kingdom have come to prominence as powerful new agents. Their reach and influence in the contemporary digital media ecology have been widely highlighted, yet there has been little scholarship to situate these important new players in the field of political communication. This article argues that, first, these 'interlopers' known as the 'alt-right' and 'alt-left' need to be understood as embedded in the context of populist politics. Second, 'hyperpartisan' describes these sites better than the framework of alternative media as it mirrors populism's ideological pillar of 'us' versus 'them'. Finally, a deliberate provocation is argued to name these digital start-ups as news to create a starting point for conceptualising these disruptive new media forces.